(untitled) (Світ фінансів, 2017)
Коваль С. Л. Базель ІІ: аналіз основних положень та можливості їх впровадження в Україні. Розглянуто основні положення “Міжнародної конвергенції розрахунку власного капіталу і вимог до власного капіталу: доопрацьованої рамкової угоди” (Базель ІІ). Виокремлено проблеми, пов’язані із забезпеченням умов впровадження положення в Україні. Подано практичні рекомендації щодо втілення окремих положень Базеля ІІ у вітчизняну банківську практику. Koval S. Basel II: the analysis of main principles and means to introduce theirs in Ukraine. Main principles of International convergence of calculation of property asset and requirements to the property asset: finished off scope agreement (Basle II) are considered. The problems of terms providing of introduction of principles in Ukraine are selected. Practical recommendations in relation to embodiment of separate principles of Basel II in domestic practice are offered.